2017
DOI: 10.1002/hep4.1083
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N‐methyltransferase expression decreases in iron overload, exacerbating toxicity in mouse hepatocytes

Abstract: Iron overload causes the generation of reactive oxygen species that can lead to lasting damage to the liver and other organs. The goal of this study was to identify genes that modify the toxicity of iron overload. We studied the effect of iron overload on the hepatic transcriptional and metabolomic profile in mouse models using a dietary model of iron overload and a genetic model, the hemojuvelin knockout mouse. We then evaluated the correlation of nicotinamide N‐methyltransferase (NNMT) expression with body i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Therefore, a putative role of NNMT as an important regulatory enzyme involved in a proper endothelial functioning has been considered, and it was a reasonable justification of our study. It was also found that an overexpression of NNMT reduces oxidative stress under various pathological conditions (Koppe et al, 2017;Xie et al, 2016). Postulated decrease in SAM concentration due to a stimulation of NNMT activity was expected to reduce protein methylation while less NAD + could limit protein F I G U R E 5 Effect of atorvastatin and pravastatin on AMPK, ACC phosphorylation, Sirtuin1, Sirtuin3 and NNMT.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a putative role of NNMT as an important regulatory enzyme involved in a proper endothelial functioning has been considered, and it was a reasonable justification of our study. It was also found that an overexpression of NNMT reduces oxidative stress under various pathological conditions (Koppe et al, 2017;Xie et al, 2016). Postulated decrease in SAM concentration due to a stimulation of NNMT activity was expected to reduce protein methylation while less NAD + could limit protein F I G U R E 5 Effect of atorvastatin and pravastatin on AMPK, ACC phosphorylation, Sirtuin1, Sirtuin3 and NNMT.…”
Section: Discussionmentioning
confidence: 99%
“…Koppe, et al found that hepatic nicotinamide levels were significantly increased by a dietary iron challenge in mice (116). This was possibly due to iron-induced downregulation of nicotinamide N-methyltransferase (NNMT) in hepatocytes (116). Additionally, hepatic NNMT expression was negatively correlated with serum iron parameters in obese individuals (116).…”
Section: Niacinmentioning
confidence: 99%
“…Koppe, et al. found that hepatic nicotinamide levels were significantly increased by a dietary iron challenge in mice ( 116 ). This was possibly due to iron-induced downregulation of nicotinamide N -methyltransferase (NNMT) in hepatocytes ( 116 ).…”
Section: Prevention Of Iron-induced Liver Damage By Nutrientsmentioning
confidence: 99%
See 2 more Smart Citations